1982
DOI: 10.1021/i100005a003
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and oxidative desorption of hydrogen sulfide by molybdenum trioxide-titanium dioxide

Abstract: A mixed oxide of Mo03 and Ti02 has been found to adsorb hydrogen sulfide and to be regenerated easily by an oxidative desorption process. The adsorbent takes up nearly one mole of H2S per mole of Mo03 according to the following two reactions: H2S + Mo03 = Mo03*SH2 and + Mo03 = Mo02-S + H20. The oxidative desorption is performed by introducing an oxygen-containing gas through the adsorbent bed. The desorbed gas contains S02 as well as a small amount of elemental sulfur. A cyclic test was carried out to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Matsuda et al 18 suggested two types of oxide adsorbents for H 2 S adsorption, i.e., non-regenerable and regenerable. ZnO, CuO, and Fe 2 O 3 are commonly known as non-regenerable adsorbents, which support the irreversible H 2 S sensing behavior of pure ZnO NW sensors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matsuda et al 18 suggested two types of oxide adsorbents for H 2 S adsorption, i.e., non-regenerable and regenerable. ZnO, CuO, and Fe 2 O 3 are commonly known as non-regenerable adsorbents, which support the irreversible H 2 S sensing behavior of pure ZnO NW sensors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conversion from sulde to oxide upon exposure to air generally takes a prolonged time, or leads to incomplete recovery. In contrast, MoO 3 is known to form non-reactive adsorption compounds, such as MoO 3 $SH 2 and MoO 2 $S, by reaction with H 2 S at 100-300 C and the oxide surface can be easily regenerated by the desorption of H 2 S. 18 This relatively easy adsorption of H 2 S on the surface of Mo oxides suggests a chemical affinity between the two, which may be the reason for the high selectivity and response to H 2 S in the Mo-doped ZnO NW sensor. The high selectivity and response to H 2 S observed in the Mo-doped ZnO NW sensor of the present study can therefore be attributed to the high chemical affinity of Mo oxide to H 2 S, and the regenerable adsorption/desorption of the Mo oxide surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 In contrast, MoO 3 is known to form nonreactive adsorption compounds such as MoO 3 $SH 2 and MoO 2 $S at 100-300 C, and the material surface can be regenerated by the desorption of sulfur-containing surface species. 41 This shows that MoO 3 is a promising material for detecting H 2 S in a highly reversible manner. Moreover, acidic MoO 3 can enable the detection of other offensive odors with alkaline nature, such as those of TMA and NH 3 .…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, Mo-doped ZnO NWs exhibited complete recovery and stable sensing characteristics as well as enhanced gas response to H 2 S throughout a wide range of operating temperatures (Figure 5(g-1–g-4)). MoO 3 is known to form regenerable adsorbents that do not go through reactive adsorption and conversion to sulfide when exposed to H 2 S [97], which explains the reversible sensing characteristics of Mo-doped ZnO NW sensors. This suggests that not only the chemical affinity between additives and analyte gas but also the adsorption species on additives should be taken into account for selective and reversible sensing characteristics.…”
Section: Physicochemical Modifications For the Enhancement Of Selementioning
confidence: 99%